South African foreign policy in Africa - Guelke, Adrian (Department of Political Studies, 2016)
In order to take account of the radical change in South Africa's international and continental environment, I have divided this thesis under two headings; policy towards colonial Africa (broadly, the period 1910 - 1959) and secondly, policy towards independent Africa (1960 - ). The division is by no means an absolute one. South Africa first began to feel the pressures of decolonization soon after the end of the Second World War. These took a variety of forms; for example, India's attacks on South Africa's racial policy and the United Nations' refusal to countenance the incorporation of South West Africa into the Union. They were echoed internally by growing militancy on the part of the African National Congress in the 1950's. Similarly after 1960, by which time most of the countries of Africa had achieved independence, the remnants of colonialism remained important to South African foreign policy. Firstly, the continuing existence of the Portuguese empire has carried the colonial order into the 1970's. Secondly, the former colonial powers have continued to exercise considerable influence on their ex-colonies. In particular, France's neo-colonial hold on many of her former colonies has assumed special importance in the context of South African initiatives towards francophone Africa.